2013
DOI: 10.1016/j.jacc.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Gait Speed as a Measure of Frailty and Risk of Cardiovascular Events After Myocardial Infarction

Abstract: Among patients with ST-segment elevation myocardial infarction, slow gait speed was significantly associated with an increased risk of cardiovascular events. (Gait Speed for Predicting Cardiovascular Events After Myocardial Infarction; NCT01484158).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 28 publications
10
104
0
3
Order By: Relevance
“…Due to the measure's extensive predictive capabilities, as well as ease of administration, the original article proposed WS be considered the "sixth vital sign". Research findings continue to support this designation (Afilalo et al, 2010;Castell et al, 2013;Elbaz et al, 2013;Matsuzawa et al, 2013;Studenski et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Due to the measure's extensive predictive capabilities, as well as ease of administration, the original article proposed WS be considered the "sixth vital sign". Research findings continue to support this designation (Afilalo et al, 2010;Castell et al, 2013;Elbaz et al, 2013;Matsuzawa et al, 2013;Studenski et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…As a valid (Rydwik et al, 2012;Verghese et al, 2011), reliable (Peters, Fritz, et al, 2013;Rydwik et al, 2012), and sensitive (Goldberg & Schepens, 2011;van Iersel, Munneke, Esselink, Benraad, & Olde Rikkert, 2008) measure, WS tests have found a home in both clinical (Peel, Kuys, & Klein, 2013) and research (Graham, Ostir, Fisher, & Ottenbacher, 2008) settings. Not only is WS indicative of an individual's functional capacity (Verghese et al, 2011) and general health status (Cesari et al, 2005;Studenski et al, 2011), the measure has been shown to be predictive of a range of outcomes, including response to rehabilitation (Goldie, Matyas, & Evans, 1996), functional dependence (Purser et al, 2005;Shimada et al, 2013;Shinkai et al, 2000), frailty (Castell et al, 2013), mobility disability (Cesari et al, 2005) (Rosano, Newman, Katz, Hirsch, & Kuller, 2008), cognitive decline (Alfaro-Acha, Al Snih, Raji, Markides, & Ottenbacher, 2007) (Inzitari et al, 2007), falls (Montero-Odasso et al, 2005) (Chu, Chi, & Chiu, 2005), institutionalization (Woo, Ho, & Yu, 1999), hospitalization (Montero-Odasso et al, 2005) (Cesari et al, 2005), cardiovascular-related events and mortality (Dumurgier et al, 2009;Matsuzawa et al, 2013), as well as all-cause mortality (Studenski et al, 2011) (Blain et al, 2010). An association has been observed between slow self-selected WS and lower quality of life (Ekstrom, Dahlin-Ivanoff, & Elmstahl, 2011), decreased participation (Ekstrom et al, 2011), and presence of depressive symptoms (Brandler, Wang, Oh-Park, Holtzer, & Verghese, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, numerous investigations have demonstrated that gait speed reflects the degree of frailty well and is a useful marker for predicting the early and late clinical outcomes in patients with particular subsets of cardiovascular disease undergoing invasive cardiac surgery. [8][9][10][11] Therefore, we investigated the usefulness of gait speed as a frailty measure predicting the prognosis of patients who underwent TAVR procedures using data from a Japanese multicenter registry.…”
Section: Kano Et Al Gait Speed and Clinical Outcomes After Tavrmentioning
confidence: 99%
“…A recent 7-year cohort Adjusted for age, diabetic nephropathy, and comorbidity score study of MWS in community-dwelling elderly reported that those who walked slowly had an almost threefold higher risk for cardiovascular mortality compared to those who walked faster [6]. Several clinical studies have found that a slow walking speed is significantly associated with an increased risk of subsequent cardiovascular events in elderly patients with ischemic heart disease, independent of cardiac function and comorbid conditions [14][15][16][17]. In addition, a slow walking speed was used as an indicator of frailty or geriatric conditions as well as decreased muscle strength (weak grip), cognitive impairment, and depression [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have found that a slow walking speed is significantly associated with an increased risk of subsequent cardiovascular events in elderly patients with ischemic heart disease, independent of cardiac function and comorbid conditions [14][15][16][17]. In addition, a slow walking speed was used as an indicator of frailty or geriatric conditions as well as decreased muscle strength (weak grip), cognitive impairment, and depression [16,17]. Our findings are consistent with those reported by previous studies of elderly patients with chronic heart disease.…”
Section: Discussionmentioning
confidence: 99%